The Effect of Toxic Leadership on Turnover Intention among Retail Employees in Indonesia: A Post-COVID-19 Quantitative Study - Ahmad Rais Habib; Josafat Gracia Ginting; Muhaidir Ikram (Yayasan Literasi Sains Indonesia, 2026)
This quantitative study analyzes the influence of toxic leadership on turnover intention in the retail sector in Indonesia in the post-COVID-19 context. Using an explanatory research approach with the PLS-SEM method, data were collected from 170 employees through a purposive sampling technique. The analysis results show that toxic leadership has a very strong positive and significant influence on turnover intention ( β = 0.850, t = 16.440, p < 0.001). Toxic leadership is able to explain the variation in turnover intention by 72.0%, The effect size value of f² = 2.550 indicates a very large effect. Key findings indicate that the Negative Spiritual State which is toxic leadership dimension is the most dominant behavioral manifestation. This is characterized by negative emotional outbursts in leaders, such as high volume, erratic moods, and inconsistent behavior that create uncertainty for subordinates. Retail companies must prioritize improving the quality of first-line leadership and establishing safe feedback mechanisms. Without intervention in leadership culture, other employee retention strategies will be difficult to maintain effectively, which may threaten the company’s operational stability.